Outcome of Pantalar Fusion With Femoral Head Allograft in Avascular Necrosis of Talus - Ramu, Thiru Karthikeyan; Bajuri, Mohd Yazid; Hayyun, Muhammad Fathi; Mazli, Norliyana (Frontiers in Surgery, 2021)
Background: Avascular necrosis (AVN) of the talus is a challenging condition that is caused primarily by trauma. The severity of the talus fracture determines the risk of AVN. Severe osteonecrosis with the loss of talar integrity can be treated with arthrodesis and structural bone graft. Method: This study shows the experience of pantalar arthrodesis using hindfoot arthrodesis nail, screw fixation, and femoral head allograft in four patients. Result: All patients were satisfied in terms of pain and function after an average of 4 months postsurgery. Limb length discrepancy was <1 cm and hindfoot fusion was achieved by 3 months. The mean score for SF-36 physical function and AOFAS hindfoot score at a 2-year postpantalar arthrodesis was 88 and 80.8, respectively. Conclusion: Hindfoot ankle arthrodesis, with the usage of femoral head allograft, can be successfully used for the treatment of traumatic AVN of talus.